Pengaruh Lingkungan Kerja dan Budaya Organisasi terhadap Kinerja Karyawan Bagian Produksi pada PT. Setya Kuliner Mandiri Jakarta Selatan - Darmadi, Darmadi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Employee performance is a crucial factor in achieving organizational goals, and it is influenced by various internal factors, including the work environment and organizational culture. This research was conducted to examine whether the work environment and organizational culture have a positive and significant effect, either partially or simultaneously, on employee performance. The study was motivated by the observation that a supportive work environment and strong organizational values are often linked to higher productivity and employee engagement. This research used a quantitative approach with a survey method. The population consisted of all production department employees at PT. Setya Kuliner Mandiri Jakarta, totaling fifty individuals. The sampling technique used was a saturated sample, where the entire population was involved as the sample. Data were collected through a closed-ended questionnaire using a Likert scale. Data analysis was carried out using multiple linear regression with the help of SPSS version 22. The data testing stages included descriptive analysis, validity and reliability tests, classical assumption tests, and multiple regression analysis (both partial and simultaneous tests). The results showed that both the work environment and organizational culture had a positive and significant influence on employee performance. These findings imply that management should continuously enhance the physical, psychological, and social aspects of the work environment, and reinforce organizational values to foster better performance among employees.